SEROPREVALENCE OF Toxoplasma gondii IN STRAY CATS (Felis domesticus) IN KHARTOUM AREA - Elmubarak, Suha.I.; M.Saad, Amir (Journal of Veterinary Medicine and Animal Production, 2021)
This work was conducted to detectToxoplasma gondii antibodies in 50 stray cats inKhartoum, using the Latex Agglutination Test LAT (slide usage).The result showed that 12 samples,representing 24% were positive to Toxoplasma gondii antibodies.The seroprevalence of the positive cases in the females was 8 out of the 33 cats(24.2%), while 4 cases were seropositive out of the 17males(23.5%).The seroprevalence of the positive cases in the adult cats was 7 out of the 29(24.1%), while 5 cases were positive out of the 21 juvenile and kitten examined(23.8%).The study indicated no noticeable difference in prevalence between the two sexes and between adults and juvenile cats.